Analisis Financing To Deposit Ratio, Debt To Equity Ratio, Return On Equity Dan Quick Ratio Terhadap Pembiayaan Murabahah Pada Bank Umum Syariah Di Indonesia - Nurdiwaty, Diah; Faisol, Faisol (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2017)
Murabaha financing is a form of channeling funds of Islamic banks in transaction using the contract of sale and purchase of goods, where the selling price at cost plus agreed profit and the seller must disclose the acquisition cost of the goods to the buyer, the payment of Murabaha can be made by cash or deferred / credit , This study was conducted to analyze the effect of Financing to Deposit Ratio (FDR), Debt To Equity Ratio (DER), Return on Equity (ROE) and the Quick Ratio (QR) on the financing Murabaha of Islamic Banks in the period of 2012-2015. Data analysis technique used is multiple linear regression analysis with a confidence level of 5%. The data used is secondary data obtained from the publication of the quarterly financial statements are recorded in the Bank Indonesia (BI). This study uses quarterly reports the population of the entire Islamic Banks registered in Bank Indonesia (BI) in 2012-2015 a total of 11 Islamic banks. The sampling technique used was purposive sampling were then obtained 64 samples of the quarterly financial statements. The results showed that partially FDR, ROE and QR significant and positive impact on the financing murabaha, while DER has significant and negative effect on murabaha financing. Based on F test showed that the FDR, DER, ROE and QR simultaneously affect the financing murabaha, the influence of these four variables independet was 43.7% and the remaining 56.3% influenced by other variables outside the research. Based on the conclusions on the outcome of this study, the authors suggest that in the decision the distribution of murabaha financing not only consider Financing to Deposit Ratio (FDR), Debt To Equity Ratio (DER), Return on Equity (ROE) and the Quick Ratio (QR), but should consider other factors, so that the decision could be more precise and accurate.